Endogenous ways to stimulate brown adipose tissue in humans. (March 2015) - Broeders, Evie; Bouvy, Nicole D.; van Marken Lichtenbelt, Wouter D.
Abstract Obesity is the result of disequilibrium between energy intake and energy expenditure (EE). Successful long-term weight loss is difficult to achieve with current strategies for the correction of this caloric imbalance. Non-shivering thermogenesis (NST) in brown adipose tissue (BAT) is a possible therapeutic target for the prevention and treatment of obesity and associated metabolic diseases. In recent years, more knowledge about the function and stimulation of bat has been obtained. The sympathetic nervous system (SNS) is currently seen as the main effector for brown fat function. Also, interplay between the thyroid axis and SNS plays an important role in BAT thermogenesis. Almost daily new pathways for the induction of BAT thermogenesis and 'browning' of white adipose tissue (WAT) are identified. Especially the activation of BAT via endogenous pathways has received strong scientific attention. Here we will discuss the relevance of several pathways in activating BAT and their implications for the treatment of obesity. In this review we will focus on the discussion of the most promising endocrine and paracrine pathways to stimulate BAT, by factors and pathways that naturally occur in the human body.